2008
DOI: 10.1353/jda.2008.0015
|View full text |Cite
|
Sign up to set email alerts
|

Macroeconomic Determinants of Migrant Remittances to Caribbean Countries: Panel Unit Roots and Cointegration

Abstract: This article examines the macroeconomic factors influencing the flow of remittances to selected English-speaking Caribbean countries. A balanced two way fixed effects (FE) model, a random effects (RE) model and the adjusted fully modified ordinary least squares (FMOLS) model (designed to correct biases in OLS)are employed in estimating a relationship between per capita remittances and selected macroeconomic variables. This article also examines the time series properties of the data within a panel unit root an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0
1

Year Published

2008
2008
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 28 publications
0
10
0
1
Order By: Relevance
“…This problem is aggravated in a panel data framework due to potential dynamic heterogeneity over the cross sections. The study of Alleyne et al (2008) showed how the fully modified ordinary least squares (FOMLS) can be adjusted to make inferences in cointegrated panels with heterogeneous dynamics, while overcoming the problems in OLS, including endogeneity. In our model, we used Chami et al (2003) method of two-stage least squares to address the issue of endogeneity.…”
Section: Estimating the Cyclicality Of Remittancesmentioning
confidence: 99%
See 2 more Smart Citations
“…This problem is aggravated in a panel data framework due to potential dynamic heterogeneity over the cross sections. The study of Alleyne et al (2008) showed how the fully modified ordinary least squares (FOMLS) can be adjusted to make inferences in cointegrated panels with heterogeneous dynamics, while overcoming the problems in OLS, including endogeneity. In our model, we used Chami et al (2003) method of two-stage least squares to address the issue of endogeneity.…”
Section: Estimating the Cyclicality Of Remittancesmentioning
confidence: 99%
“…In this equation, ρ e could capture the UIP disturbances or effects of persistent movements in the risk premium. Equation 4then feeds into the BSP reaction function in equation (1). To determine the link between the real exchange rate and the nominal exchange rate, it is assumed that deviations from purchasing power parity occur in the short-run.…”
Section: A Structure Of the Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…The relevance of the model to developing economies can be enhanced by further adaptation of the balance of payments constraint to include two important aggregates: net interest payments (Moreno‐Brid, 2003) and net transfers. The latter is particularly important as, unlike other forms of capital inflows, net transfers have no corresponding obligations and it is largely a consequence of nationals migrating to developed countries and sending back foreign exchange (Alleyne et al. , 2008).…”
Section: Further Adaptation Of the Modelmentioning
confidence: 99%
“…Metroeconomica 59:2 (2008) 189-202 doi: 10.1111/j.1467-999X.2008.00299.x important source of capital inflow for many developing countries. Net transfers have surpassed development assistance and are more stable than foreign direct investment and thus must be treated as a separate resource inflow (Ratha, 2005;Giuliano and Riuz-Arranz, 2006;Alleyne et al, 2008).…”
Section: Introductionmentioning
confidence: 99%